Following the water : environmental history and the hydrological cycle in colonial Gippsland, Australia, 1838-1900 - Carman-Brown, Kylie (ANU Press, 2019)
Water reflects culture. This book is a detailed analysis of hydrological change in Australia's largest inland waterway in Australia, the Gippsland Lakes in Victoria, in the first 70 years of white settlement. Following air, water is our primal need. Unlike many histories, this book looks at the entire hydrological cycle in one place, rather than focusing on one bit. Deftly weaving threads from history, hydrology and psychology into one, Following the Water explores not just what settlers did to the waterscape, but probes their motivation for doing so. By combining unlikely elements together such as swamp drainage, water proofing techniques and temperance lobbying, the book reveals a web of perceptions about how water 'should be'. With this laid clear, we can ask how different we are from our colonial forebears.